The Pursuit of The Target Capital Structure: An Empirical Study of Pharmaceutical Companies Listed in The SEC - Saiwiwat, Paweena (2009)
Capital structure has been one of the most controversial issues in the ground of finance during past decades. Although there have been a number of existing theories and empirical studies observing patterns involved in choosing a capital structure, until now, there is no universal one. In this regard, this dissertation attempts to explain the capital structures. The capital structures in this case involve the study of 6 ratios regarding to debt-to-equity, debt-to-assets, and equity-to-assets, or this research can be called the study of debt-equity structures.